Stepwise cooling and thickness of sliced pineapple fruit in subcooling tolerance - Dibirasulaev, M A; Belozerov, G A; Dibirasulaev, D M; Donetskikh, A G; Umaralieva, L B (IOP conference series. Earth and environmental science, 2022)
Chilled foods have a number of nutritional and biological advantages over frozen foods. Consumer preferences for chilled foods are based on the fact that they are less processed and more suitable for cooking than frozen foods. Numerous studies on cold preservations of foods proposed alternative methods of extending shelf life, including those based on subcooling (cooling below normal boiling point without phase change). Analytical studies show that subcooling has a number of advantages for extending shelf life of foods. An advantageous aspect of supercooled food storage involves lower energy costs for its industrial application, compared to partially frozen storage. Storing foods in a temperature range from cryoscopic to nucleation is called NFTS (near freezing temperature storage). Biochemical, microbiological and organoleptic indicators confirmed extended shelf life of plants stored through NFTS technology. The paper presents the findings to evaluate the effect of step cooling and the thickness of sliced pineapple on subcooling and storage persistence. A series of experimental studies indicate a significant distinction between cryoscopic and maximum supercooling temperature of pineapple slices, subject to geometry and availability of packaging, and a relationship between cooling rates, degree of subcooling and subcooling tolerance in pineapples.